Providence and the affective benefits of natural causality - Jordan, PN (University of Chicago Press, 2022)
Stories of science as an engine of secularisation generally assume that scientific ideas and traditional religion are incompatible with each other, such that the advance of the former necessarily means the retreat of the latter. In certain versions of these stories, fear heightens the tension in the plot by accounting for why religion exists in the first place. This article looks at a range of early modern English thinkers, including Walter Charleton, John Spencer, and Joseph Glanvill, for whom the application of a key feature of science and its historical precursors—the explanation of phenomena through natural causality—is by contrast helpful, because it allows them to battle improper fears within Christianity. Their goal in pursuing naturalistic explanations is not the elimination of fear altogether, but rather the elimination of misplaced fears generated by a misunderstanding of how God works in the world. This promotion of some views of God’s activity in nature over others is a consequence of what they perceive to be the affective implications of different versions of the doctrine of providence. Even though these authors may not have imagined the expansion of natural causality’s explanatory scope to lead to secularisation, their ideas inadvertently helped to prepare the ground for at least one later instance of it: the secularisation of science itself.